EFEKTIVITAS STRAIN BRADYRHIZOBIUM JAPONICUM YANG DIISOLASI DARI BEBERAPA LOKASI DI ENDE TERHADAP PEMBENTUKAN NODUL DAN PENAMBATAN NITROGEN PADA TANAMAN KEDELAI (GLYCINE MAX L.) - Kristina Erniyani (Agriculture Faculty of Flores University, 2010)
Bacteria Bradyrhizobium spp. From nodules on soybean plants, bind nitrogen from the air and make it freely available to plants. Amount of nitrogen fixed depends on the ability of a strain to form nodules, nodule effectiveness and environmental conditions. On land – land that had been planted with soybeans, inoculation with Bradyrizhobium bacteria are often not required. To test these lands in the district of Ende, NTT has conducted an experiment with a factor in the design of Randomized Complete with nine treatment groups. The treatment consists of (i) inoculation with the soybean crop in the ground former Ekoae (R1), (ii) inokulasi with soil former soybean plants in Ndona (R2), (iii) inoculation of soybean plants with the soil used in Flores (R3), (iv) Brady rhizobium isolates from soybean nodules in Ekoae (R4), (v) Bradyrhizobium isolates from nodules of soybean plants is in Ndona (R5), (v) Bradyrhozobium isolates from nodules of soybean plants at Flores (R6) (vii) a commercial inoculant legin (L), (viii) fertilizer nitrogen (N), and (ix) Control (K). all treatments were repeated 4 times. Land used in these experiments is the land of Ndona. The experiment was carried out since faculty, Udayana University. The highest percentage of effective nodules on the treatment Bradyrhizobium isolates from sybean nodules in Ndona (R5). Total nitrogen levels at the age of 45 HST in the highest in soybean plants that received 100 kg ha-1 urea and soybeans that have a desolate Bradyrhizobium inoculation of soybean nodules in Ndona (R). Efficiency and levels of symbiotic nitrogen fixation result obtained highest in soybean plants that received an inoculation Bradyrhizobium diisolat soybean nodules in Ndona (R5). Oven dry weight of plants that from the age of 45 HST on all isolates are equivalent to the oven-dry weight of plants at the fertilization of 100 kg ha- 1 urea. The result shoed that the land – the land of Ekoae, Ndona and Fkres have high Bradirhizobium contain bacteria. Bacteria Bradyrhizobium cp. Most numerous in the isolates from soybean nodules in Ndona (R5) the most efficient from effective nodules is 82.26% and as high as the 0.52% N fixate. These results indicate that isolates from Ndona Bradyrhizobiun veeb able to form effective nonudel on yoy beans grown in soil from Ndona. The result also indicates inoculation with a commercial inoculant was obtained not on land – land planted with soybeans used